Toxicity of Sida rhombifolia L. 96% ethanol extract based on LD50 and macropathological examination of mice's organs - Aulena, Desi Nadya; Kumala, Shirly; Abdillah, Syamsudin; Rahmat, Deni; Zaidan, Sarah; Fitriyani, Dwi; Raihan, Dany (Faculty of Pharmacy, Universitas Pancasila, 2024)
The Indonesian people empirically use Sidaguri (Sida rhombifolia L.) in medicine, such as anti-hyperuricemia. Herbal-based treatment is currently much preferred. Drug metabolism, in general, mainly occurs in the liver, so the possibility of damage to this organ is high. This study aims to determine the acute toxicity category of 96% ethanol extract of sidaguri based on the LD50 value, changes in body weight, changes in organ weight, and macro pathology in the organs of male DDY mice in vivo. The method used in this research was experimental with a fixed dose design following the Indonesian Food and Drug Authority regulations regarding guidelines for in vivo non-clinical toxicity tests. The test group was divided into six dose groups (standard, 50, 300, 2000, 5000, and 15000 mg/kg Body of weight). Observations were made for 24 hours. Observations were continued for 14 days on death parameters, toxicity symptoms, body weight, and relative organ weights using five main organs (heart, lungs, liver, spleen, and kidneys, and pathological examination). The acute toxicity test results showed no death in all dose treatment groups. Macropathological analysis did not show abnormalities in organs in all groups of mice. LD50 value is more than 15000 mg/kg. Sidaguri 96% ethanol extract is safe and Practically non-toxic.